2017
DOI: 10.18805/ijar.b-646
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short-mid-long term intravaginal sponge application on reproductive performance of karacabey Merino ewes in the anestrous season

Abstract: The aim of the present paper was to investigate the efficiency of different progestagen treatment methods in combination with Pregnant Mare Serum Gonadotrophin (PMSG) in Merino ewes outside the breeding season. A total of 78 ewes (2 to 4 years old) with a mean bodyweight of 58.4 kg and an average body condition score (BCS) of 3.5 were used in the trial. The ewes were randomly divided into 3 equal groups [n= 26]. Intravaginal progestagen sponges containing Fluorogestone Acetate (FGA; 30 mg) were inserted intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The percentage of estrous ewes treated with progestogen sponge for a long term (14 days) was significantly higher than that of ewes treated for 7 and 10 days ( P < 0.05) ( 17 ). In this study, there was no significant difference in the total percentage of estrous ewes treated with different protocols of estrus synchronization, and there was no significant difference in the proportion of estrous ewes in any one of the five time periods within 72 h after withdrawal of the sponge among five protocols.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The percentage of estrous ewes treated with progestogen sponge for a long term (14 days) was significantly higher than that of ewes treated for 7 and 10 days ( P < 0.05) ( 17 ). In this study, there was no significant difference in the total percentage of estrous ewes treated with different protocols of estrus synchronization, and there was no significant difference in the proportion of estrous ewes in any one of the five time periods within 72 h after withdrawal of the sponge among five protocols.…”
Section: Discussionmentioning
confidence: 91%
“…It was reported that the lambing rate of ewes treated with FGA (30 mg) for 14 days was significantly higher than that of ewes treated for 7 days ( P < 0.05) ( 17 ), indicating that the long period treatment of the FGA intravaginal sponge was conducive to lambing rate of ewes. It is worth noting that the breeders usually wish the twinning lamb because compared with multi-lamb, twinning lamb has larger birth weight, easier survival, and better growth ( 36 ), which is especially conducive to the breeding and management of large-scale sheep farms.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Different rates of estrus induction and pregnancy have been reported in various studies using CIDRs and sponges. Altinçekiç and Koyuncu (2019) used FGA sponges (30 mg) and 500 IU eCG at sponge withdrawal for estrus induction in Merino ewes during the anestrus season for different periods (7, 10, and 14 days). They observed estrus behaviour in 65.4, 80.8 and 96.2 percent of treated ewes in short, mid and long‐term groups.…”
Section: Discussionmentioning
confidence: 99%
“…They observed estrus behaviour in 65.4, 80.8 and 96.2 percent of treated ewes in short, mid and long‐term groups. Also, the lambing rate was 61.5, 88.5 and 92.3 percent respectively (Altinçekiç & Koyuncu, 2019). Likewise, Swelum et al (2015) compared CIDR and FGA sponges (30 mg) in estrous synchronization and hormonal profiles of Najdi ewes during the breeding season.…”
Section: Discussionmentioning
confidence: 99%